Enhancing Project Visibility: A Study on Construction Project Dashboard Development with Extreme Programming - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research aims to improve the visibility and effectiveness of construction project management by developing a project dashboard using the Extreme Programming (XP) approach. The focus of this research is to design and implement an intuitive, responsive, and adaptive project dashboard to support real-time monitoring of project progress. XP methodology was integrated to deliver flexible and high-quality software development. The research included an analysis of the complexity of construction projects, emerging management challenges, and visibility limitations in construction projects. In addition, the research defines the project dashboard as a crucial visualization tool to increase transparency and user engagement. Innovation through the Extreme Programming (XP) approach was introduced, focusing on introducing the basic principles of XP and their relevance in construction software development. The results of testing the application features showed positive responses, both in technical and functional terms. Technology acceptance testing validated the successful integration of IoT technologies, data security, and application performance. By involving users in alpha and beta tests, the research gained valuable feedback to improve the app before the official launch. The research confirmed that the development of a construction project dashboard using the XP approach has the potential to improve the visibility, transparency, and effectiveness of construction project management. This research contributes to the practical and theoretical understanding of dealing with the complexity of construction projects by utilizing innovative software development technologies and methodologies.